Integrated Analysis of Microarray and RNA-Seq Data for the Identification of Hub Genes and Networks Involved in the Pancreatic Cancer - Nisar, Maryum; Paracha, Rehan Zafar; Arshad, Iqra; Adil, Sidra; Zeb, Sabaoon; Hanif, Rumeza; Rafiq, Mehak; Hussain, Zamir (Frontiers in Genetics, 2021)
Pancreatic cancer (PaCa) is the seventh most fatal malignancy, with more than 90% mortality rate within the first year of diagnosis. Its treatment can be improved the identification of specific therapeutic targets and their relevant pathways. Therefore, the objective of this study is to identify cancer specific biomarkers, therapeutic targets and their associated pathways involved in the PaCa progression. RNA-seq and microarray datasets were obtained from public repositories such as the European Bioinformatics Institute (EBI) and Gene Expression Omnibus (GEO) databases. Differential gene expression (DE) analysis of data was performed to identify significant differentially expressed genes (DEGs) in PaCa cells in comparison to the normal cells. Gene co-expression network analysis was performed to identify the modules co-expressed genes, which, are strongly associated with PaCa and as well as the identification of hub genes in the modules. The key underlaying pathways were obtained from the enrichment analysis of hub genes, and studied in the context of PaCa progression. The significant pathways, hub genes and their expression profile were validated against The Cancer Genome Atlas (TCGA) data, and key biomarkers and therapeutic targets with hub genes were determined. Important hub genes identified included: ITGA1, ITGA2, ITGB1, MET, LAMA3, LAMC2, THBS and TGFβ1 etc.. Enrichment analysis characterizes the involvement of hub genes in multiple pathways. Important ones determined are ECM-receptor interaction, and focal adhesion pathways. The interaction of overexpressed surface proteins of these pathways with extracellular molecules initiates multiple signaling cascades. Including stress fiber and lamellipodia formation, PI3K-Akt, MAPK, JAK/STAT and Wnt signaling pathways. Identified biomarkers may have a strong influence on the PaCa early stage development and progression. Further, analysis of these pathways and hub genes can help in the identification of putative therapeutic targets and development of effective therapies for PaCa.